Transition Metals in Organic Synthesis, Part 111: First Total Synthesis and Structural Revision of Antipathine A - Berndt, Andreas; Gruner, Margit; Schmidt, Arndt W.; Knölker, Hans-Joachim (Synlett, 2013)
We describe the first total synthesis of antipathine A and a revision of the original structural assignment.
Keywords: alkaloids; catalysis; cyclisation; palladium